Collection of Zakat for Civil State Employees According to Islamic Law and Law - Nurhadi Nurhadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2020)
The history sheet reveals the development of formal legal amil zakat in Indonesia in 1968 the ratification of Minister of Religion Regulation (PMA) Number 4 of 1968 concerning the Establishment of the Amil Zakat Agency (BAZ) and PMA Number 5 of 1968 concerning the Establishment of Baitul Maal (PBM). Precisely on December 12, 1989 was issued the Instruction of the Minister of Religion (Inpres) 16/1989 concerning the Development of Zakat, Infaq and Shadaqah (PZIS). Then in 1998-1999 and 2001-2003 BAZNAS was formed with the Presidential Decree so that in 2011 the rule of zakat processing emerged namely Law Number 23 of 2011. Through this formal law the author will examine the terminology of amil zakat according to Islamic Law and Law. Amil zakat is a person who is involved or actively participates in zakat activities, starting from collecting zakat from muzaki to distributing it to mustahiq. Legal arrangements in Indonesia relating to the competence of amil zakat are very important in neglecting zakat funds and channeling them to mustahiq, but must be supported by the authorities. Islamic law considers the competence of amil zakat to be very urgent, with accountable amil. While the government is very competent in increasing Baznas income annually, supported also by the fatwa of the Indonesian Ulema Council (MUI) regarding the government's obligation to cut salaries for civil servants / ASNs to be more effective in raising zakat funds and Baznas will be more maximal in alleviating poverty and welfare of society and ummah as extension of the government to the welfare of the people.